A noninterference trusted dual system security guarantee method based on secure memory. (12th November 2022) - Hong, Yu; Li, Yi; Tan, Haining
Summary: With the continuous maturity and development of single hardware security mechanism, it has been widely used in the field of information technology, but the single hardware mechanism has insufficient security guarantee in its own supporting drivers and other key programs. In response to this problem, this article proposes a trusted isolation model based on the noninterference theory and gives a formal proof. The realization is based on the trusted platform control module (TPCM) hardware mechanism by introducing a secure memory bar to provide a way to achieve a trusted dual‐system isolation guarantee. The hardware interface of secure memory module is consistent with that of ordinary memory module, which is widely used. It can improve the security guarantee ability of trusted computing platform, and has a good reference value for the design and application of trusted computing platform equipment.